2012
DOI: 10.1111/j.1360-0443.2011.03700.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of standard methadone treatment compared to initiating methadone without counseling: 12‐month findings

Abstract: Aims This study aimed to determine the relative effectiveness of 12-months of Interim Methadone (IM; supervised methadone with emergency counseling only for the first 4 months of treatment), Standard Methadone treatment (SM; with routine counseling) and Restored Methadone treatment (RM: routine counseling with smaller caseloads). Design A randomized controlled trial was conducted comparing: IM, SM, and RM treatment. IM lasted for 4 months after which participants were transferred to SM. Setting The study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 23 publications
(24 reference statements)
2
83
1
Order By: Relevance
“…These reductions in risk behavior were generally comparable across groups, with one exception: the interim treatment group showed greater reductions in criminal activity than the standard methadone group at the 2-month timepoint (p<.05). Finally, the authors conducted a subsequent 12-month follow-up assessment, which translated to 8 months after the interim group had been transitioned to standard methadone treatment (Schwartz et al, 2012). At this second evaluation, there were no differences between the interim, standard and restored methadone groups in treatment retention (60.6%, 54.8% and 37.8%, respectively; p=.09) or percent of heroin-positive urine specimens (46%, 48% and 51%, respectively; p=.91).…”
Section: Methodsmentioning
confidence: 99%
“…These reductions in risk behavior were generally comparable across groups, with one exception: the interim treatment group showed greater reductions in criminal activity than the standard methadone group at the 2-month timepoint (p<.05). Finally, the authors conducted a subsequent 12-month follow-up assessment, which translated to 8 months after the interim group had been transitioned to standard methadone treatment (Schwartz et al, 2012). At this second evaluation, there were no differences between the interim, standard and restored methadone groups in treatment retention (60.6%, 54.8% and 37.8%, respectively; p=.09) or percent of heroin-positive urine specimens (46%, 48% and 51%, respectively; p=.91).…”
Section: Methodsmentioning
confidence: 99%
“…This raises the question of whether combining or sequencing potent ingredients of ABT and MAT may produce outcomes superior to either used in isolation. Studies that have attempted Downloaded by [New York University] at 03:09 21 July 2015 such combinations, including combining methadone maintenance with varied levels of counseling or psychotherapy (Gruber, Delucchi, Kielestein, & Batiki, 2008;McLellan, Woody, Luborsky, & Goehl, 1988;Schwartz, Kelly, O'Grady, Gandhi, & Jaffe, 2011), ancillary social services (McLellan et al, 1998), recovery mutual aid participation (White et al, 2014), or concurrent treatment in a therapeutic community (De Leon et al, 1995;Sorensen et al, 2009), have produced promising but mixed results. Such studies need to be continued using different combinations of pharmacotherapy and psychosocial recovery support in different cultural contexts.…”
Section: Discussionmentioning
confidence: 96%
“…Schwartz et al [31] found no differences in 12-month outcomes of patients on standard methadone treatment with routine counseling and those who received no counseling. In addition, Mitchell et al [24] did not find differences in buprenorphine-maintained patients on intensive or standard outpatient treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid maintenance can be viewed as a platform for interactions to support recovery [31], but the optimal psychosocial intervention is a matter of debate, and the use of psychosocial interventions varies significantly across Europe (www.emcdda). Best practice WHO guidelines recommend that psychosocial support is routinely offered alongside pharmacological treatments.…”
Section: Discussionmentioning
confidence: 99%